First we find the values for the function g in the interval [-2,1].
x = -2
![g(-2)=-20((1)/(2))^(-2)+10=-70](https://img.qammunity.org/2023/formulas/mathematics/college/xzh3eydvnrke3ab6zhak4xzot2cl6s94p8.png)
x = -1
![g(-1)=-20((1)/(2))^(-1)+10=-30](https://img.qammunity.org/2023/formulas/mathematics/college/fgwzk2jxyrj8itrguu79da6fe6ous88ibt.png)
x = 0
![g(0)=-20((1)/(2))^0+10=-10](https://img.qammunity.org/2023/formulas/mathematics/college/wxiu15msw75susp27pw74eh7v0q0v6mhho.png)
x = 1
![g(1)=-20((1)/(2))^1+10=0](https://img.qammunity.org/2023/formulas/mathematics/college/39bjozxp2c5xj5etdd22nmlyndl0lmrvls.png)
Statement
Function f is increasing.
Function g is increasing.
Function f is negative.
Function g is negative.
Answer: D. Both functions are increasing, but function g increases at a faster average rate.